ANALISIS KEBUTUHAN PENGEMBANGAN BAHAN AJAR ATLETIK BERBASIS PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KETRAMPILAN BERPIKIR KRITIS MAHASISWA - Hendry Ismawan; Hamdiana; Didik Cahyono; Muhammad Rifai; Paryadi; Ahmad Junaidi (EDU RESEARCH, 2024)
Based on initial observations and interviews with lecturers teaching athletics courses, it was found that students' critical thinking skills in learning athletics were still low. This is caused by several factors, including: 1) the teaching materials used are still too lecturer-centred and have not encouraged students to think critically, 2) the learning methods applied do not involve students actively.This study aims to analyse the need for developing problem-based learning (PBL) based athletic teaching materials to improve students' critical thinking skills. The research method used is research and development with the ADDIE model which consists of 5 stages: analysis, design, development, implementation, and evaluation. The research subjects were physical education students at one of the universities in Central Java. Data collection techniques used interviews, observations, and questionnaires. The results showed that: 1) The needs analysis of PBL-based athletic teaching materials shows that teaching materials are needed that can improve students' critical thinking skills; 2) The design of PBL-based athletic teaching materials is arranged based on the curriculum and student characteristics; 3) The teaching materials developed have been declared valid by material experts and media experts; 4) The implementation of PBL-based athletic teaching materials has proven effective in improving students' critical thinking skills. The conclusion of this study is that PBL-based athletic teaching materials can improve students' critical thinking skills.